2015
DOI: 10.1093/mnras/stv1085
|View full text |Cite
|
Sign up to set email alerts
|

Does the stellar disc flattening depend on the galaxy type?

Abstract: We analyze the dependence of the stellar disc flatness on the galaxy morphological type using 2D decomposition of galaxies from the reliable subsample of the Edge-on Galaxies in SDSS (EGIS) catalogue. Combining these data with the retrieved models of the edge-on galaxies from the Two Micron All Sky Survey (2MASS) and the Spitzer Survey of Stellar Structure in Galaxies (S 4 G) catalogue, we make the following conclusions:(1) The disc relative thickness z 0 /h in the near-and mid-infrared passbands correlates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 58 publications
7
46
0
Order By: Relevance
“…These values are close to the galactic disk thickness in welldefined samples of edge-on spiral galaxies (Mosenkov et al 2015).…”
Section: General Characteristics Of the Galaxiessupporting
confidence: 77%
“…These values are close to the galactic disk thickness in welldefined samples of edge-on spiral galaxies (Mosenkov et al 2015).…”
Section: General Characteristics Of the Galaxiessupporting
confidence: 77%
“…As demonstrated by Mosenkov et al (2015), this can seriously affect the resulting galaxy parameters. Particularly striking is the huge discrepancy (more than a factor of two) between the I-band radial scale length obtained by Kregel et al (2002) compared to the one obtained by Xilouris et al (1999).…”
Section: The Targetmentioning
confidence: 99%
“…deGrijs et al (1997) showed that the photometric vertical scale height increases by 20% if the inclination i deviates from the 90 o by 5 o . We use the visibility of the dust lane in SDSS images of all selected galaxies with lags and simple technique described in Bizyaev & Kajsin (2004); Mosenkov et al (2015) to estimate the inclination. We do not see any dependence between the lag and the inclination.…”
Section: Inclination Effectsmentioning
confidence: 99%